1954
DOI: 10.1103/physrev.95.500
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Shift Calculation of High-Energy Electron Scattering

Abstract: The details of a phase-shift calculation of high-energy electron scattering by nuclei are given, together with some preliminary results. A new method for summing the Legendre series for the Coulomb scattering amplitude is described. The results indicate that the erst Born approximation does not give cross sections accurate enough for a reliable interpretation of the experiments. From a comparison of the few theoretical cross sections already obtained with the experiments in gold at 125 Mev, very tentative conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
191
0
7

Year Published

1955
1955
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(211 citation statements)
references
References 19 publications
4
191
0
7
Order By: Relevance
“…This confines our treatment to nuclei with spin 0 in the ground state. (To treat other nuclei similar modifications to those used to incorporate the liquid drop model in the collective model (Bohr 1952;Bohr and Mottelson 1953) From the analysis (Yennie, Ravenhall, and Wilson 1954;Brown and Elton 1955) of high energy electron scattering experiments (Hofstadter, Fechter, and McIntyre 1953;Hofstadter et al 1954) S is given approximately by S=(3f5)lX1'20At X 10-13 cm.…”
Section: Formulation Of the Modelmentioning
confidence: 99%
“…This confines our treatment to nuclei with spin 0 in the ground state. (To treat other nuclei similar modifications to those used to incorporate the liquid drop model in the collective model (Bohr 1952;Bohr and Mottelson 1953) From the analysis (Yennie, Ravenhall, and Wilson 1954;Brown and Elton 1955) of high energy electron scattering experiments (Hofstadter, Fechter, and McIntyre 1953;Hofstadter et al 1954) S is given approximately by S=(3f5)lX1'20At X 10-13 cm.…”
Section: Formulation Of the Modelmentioning
confidence: 99%
“…Various approximate treatments have been proposed in the past for the treatment of CC [10,12,13,14,15,16,17,18,19], and there is an extensive literature on the eikonal approximation [20,21,22,23,24]. In particular it has been shown that at lowest order, an expansion of the electron wave function in αZ leads to the well known effective momentum approximation (EMA) [9], which is explained in Sect.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, in contrast to the work of Ref. [40], we calculate the charge form factors not only within the PWBA but also in DWBA by the numerical solution of the Dirac equation [49][50][51] for electron scattering in the Coulomb potential of the charge distribution of a given nucleus. Also, now we do not neglect neutrons, as was done in Ref.…”
Section: Introductionmentioning
confidence: 99%